Summarising children's wellbeing: the LSAC Outcome Index - Sanson, A.; Misson, S.; Wake, M.; Zubrick, Stephen; Silburn, Sven; Rothman, S.; Dickenson, J. (Australian Government - Australian Institute of Family Studies, 2005)
This paper describes the development of the Outcome Index for Wave 1 of Growing Up in Australia - the Longitudinal Study of Australian Children (LSAC), and illustrates some of the ways in which it can be used to shed light on how well children are faring and how this relates to the conditions of their life.